Simulaciones magnetohidrodinámicas con conducción térmica de la reconexión en fulguraciones solares - Izquierdo Guzmán, Itzayana del Carmen (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
A detailed simulation of solar flares is conducted to study the influence of magnetic field strength and thermal conductivity on the dynamics of magnetic reconnection and energy conversion during the process. In this simulation, the Magnetohydrodynamics (MHD) equations are solved in a 2.5D model with resistivity and thermal conductivity, covering a domain spanning the chromosphere-corona interface of the Sun. The flare is intentionally initiated at a null point where a Gaussian distribution of resistivity reaches its maximum value, and its evolution is studied with respect to the mentioned parameters. The parameter space includes magnetic field strengths (B0) ranging from 22 G to 50 G, while thermal conductivity (k) varies from zero to 10-11 W m-1K-7/2. Within this parameter space, it is found that the magnetic field magnitude plays a crucial role in determining the reconnection rate, with variations of up to a hundred percent in the B0 range. Conversely, the thermal conductivity has a more limited impact, leading to a maximum ten percent variation in the rate of change. Furthermore, the evolution of magnetic, kinetic, and internal energies in a region directly above the reconnection point is calculated, and their interaction is assessed. Across all simulations, it is observed that magnetic energy initially dominates and relaxes over a timescale of about 20 seconds. During this phase, magnetic energy decreases by approximately 50 %, while internal energy increases by around 100 %. As the process unfolds, a portion of magnetic energy is transformed into kinetic energy, driving the generation of plasma motions in the form of upward-moving jets. The magnitude of these jets is greater for higher B0 values and lower k values.

Se lleva a cabo una simulación detallada de las fulguraciones solares para estudiar el impacto de la magnitud del campo magnético y la conductividad térmica en la dinámica de la reconexión magnética y la conversión de energía. Se resuelven las ecuaciones de la Magnetohidrodinámica (MHD) en un modelo 2.5D que incluye resistividad y conductividad térmica, abarcando desde la cromosfera hasta la corona solar. La fulguración se inicia deliberadamente en un punto nulo, donde una distribución Gaussiana de la resistividad alcanza su máximo. Se analiza su evolución en función de los parámetros del campo magnético (B0) y la conductividad térmica (k). El rango de B0 varía de 22 G a 50 G, mientras que k oscila entre cero y 10-11 W m-1K-7/2. Se encuentra que B0 tiene un papel crucial en la tasa de reconexión, con variaciones de hasta un 100 %. En contraste, k tiene un impacto más limitado, con un máximo de 10% en la tasa de reconexión. Se calcula la evolución de las energías magnética, cinética e interna en una región sobre el punto de reconexión. La energía magnética inicialmente domina y se relaja en aproximadamente 20 segundos, disminuyendo en un 50 %, mientras que la energía interna aumenta en un 100 %. A medida que avanza el proceso, parte de la energía magnética se convierte en energía cinética, generando chorros de plasma que se desplazan verticalmente desde el punto de inicio de la reconexión. La magnitud de los chorros es mayor con valores mayores de B0 y una menor k.
Instituto de Física y Matemáticas. Doctorado en Ciencias en el Área de Física
Keywords: info:eu-repo/classification/cti/1; IFM-D-2023-1060; Dinámica de fulguraciones; Modelos de fulguraciones; Campos magnéticos coronales; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16570